How Does a Neuron “know” to Modulate Its Epigenetic Machinery in Response to Early-Life Environment/Experience? - Karsten, Carley A.; Baram, Tallie Z. (Frontiers in Psychiatry, 2013)
Exciting information is emerging about epigenetic mechanisms and their role in long-lasting changes of neuronal gene expression. Whereas these mechanisms are active throughout life, recent findings point to a critical window of early postnatal development during which neuronal gene expression may be persistently “re-programmed” via epigenetic modifications. However, it remains unclear how the epigenetic machinery is modulated. Here we focus on an important example of early-life programming: the effect of sensory input from the mother on expression patterns of key stress-related genes in the developing brain. We focus on the lasting effects of this early life experience on corticotropin releasing hormone (CRH) gene expression in the hypothalamus, and describe recent work that integrates organism-wide signals with cellular signals that in turn impact epigenetic regulation. We describe the operational brain networks that convey sensory input to CRH-expressing cells, and highlight the resulting “re-wiring” of synaptic connectivity to these neurons. We then move from intercellular to intracellular mechanisms, speculating about the induction and maintenance of lifelong CRH repression provoked by early-life experience. Elucidating such pathways is critical for understanding the enduring links between experience and gene expression. In the context of responses to stress, such mechanisms should contribute to vulnerability or resilience to post-traumatic stress disorder (PTSD) and other stress-related disorders.